Improving the bank credit risk management by means of regulation of its branch concentration - Matyushin, O.V.; Shkaeva, T.I. (Економіка промисловості, 2014)
The article presents a scientific and methodical approach to the regulation of the industry concentration of credit risk of banks, based on the analysis and prediction of the dynamics of development of branches with different dominant products and technologies for their production. It is based on the idea that the loans to branches that are at the stage of growth and show a steady positive dynamics of output and profitability of operations are considered to be the least risky. Existing approaches and models of credit risk assessment are the market ones. Their use is fully justified in the case of acceptance of the hypothesis about the effectiveness of the stock market as an indicator of sustainability of enterprises. In modern conditions, when the stock market has lost its economic function of determining the value of companies to raise their funds, in terms of institutional and technological backwardness of the stock market the possibility of using these models are very limited. The objective of this article is to ground the scientific and methodical approach to credit risk management of the bank on the basis of regulating their branch concentration and developing on this basis practical recommendations to diversify its loan portfolio, taking into account branch factors. the developed procedure of the loan portfolio formation is the basis forthe implementation of the proposed approach to the regulation of the branch concentration of bank credit risk. It includes analyzing of the existing loan portfolio and choosing of branches to form a new portfolio, building and analyzing time series of branch revenues and profitability, calculating of risk indicators for each branch based on the limits of sales revenues and profitability in the forecast period, loan portfolio optimization by minimizing the risk, taking into account branches loan limits with achieving the expected return. The economic and mathematic model of credit portfolio formation taking into consideration a branch factor is worked out. Recommendations on bank credit risks branch concentration regulation improving is offered.